Teori Interpretasi Nasr Hamid Abu Zayd - Fikri Hamdani (Farabi, 2016)
This paper describes the thought of Nasr Hamid Abu Zayd on the theory of interpretation/method of interpretation of the al-Qur’an, the discussion of which is the study of descriptive-analitif. In the method, Nasr Hamid seeks to reveal the meaning and significance (maghza) with the meaning of "unspeakable". Nasr Hamid distinguish these three terms. Meaning is what is represented by the text or in the sense that letting the text speak about himself. then from that meaning discussed with conditions / context that surrounds a reader. Therefore, the meaning of the static nature as it contains a textual-historical significance (historical meaning), and the dynamic nature of significance according to the horizon of each reader.